Analysis of the Kyrgyz Republic's Energy Sector - World Bank (World Bank, Washington, DC, 2017)
Adequate and affordable energy supply is fundamental for economic growth, higher living standards, and social equity. The delivery of modern energy services helps to improve the quality of life for all citizens, expands opportunities for private businesses—and ultimately creates jobs. In the Kyrgyz Republic, energy is also a source of revenues when it can be produced in sufficient quantities to be exported, thereby helping to diversify the economy and open new markets.